2018
DOI: 10.1002/pen.25045
|View full text |Cite
|
Sign up to set email alerts
|

Improved environmental stability, electrical and EMI shielding properties of vapor‐grown carbon fiber‐filled polyaniline‐based nanocomposite

Abstract: An all polymeric electrically conductive thermoset adhesive resin system is prepared for future lightning strike protection applications. Polyaniline (PANI)‐based hybrid nano‐composite is prepared by incorporating high apparent‐density type vapor grown carbon fiber (VGCF‐H) as additional conductive filler. Electrical, mechanical and electromagnetic interference (EMI) shielding properties of PANI‐dodecylbenzene sulfonic acid (DBSA), and divinylbenzene (DVB) system are improved with addition of VGCF‐H. Different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Besides, the EMI shielding performance of CFRP could also be improved by being coated with conductive paints filled with metallic particles or nanowires [ 30 ], but it still meets the challenge of poor dispersion of conductive fillers and poor wear. In recent years, intrinsically conducting polymers (ICPs) have also been used as fillers for EMI shielding [ 31 , 32 , 33 ], but their poor mechanical and thermal properties limit their practical applications [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the EMI shielding performance of CFRP could also be improved by being coated with conductive paints filled with metallic particles or nanowires [ 30 ], but it still meets the challenge of poor dispersion of conductive fillers and poor wear. In recent years, intrinsically conducting polymers (ICPs) have also been used as fillers for EMI shielding [ 31 , 32 , 33 ], but their poor mechanical and thermal properties limit their practical applications [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The energy dissipation by free electrons or mobile charge carriers assists the microwave absorption. [47] It is also to be noted that the absorption property of the materials depends on their other properties like dielectric permittivity, conductivity, and permeability. On the other hand, the inhomogeneity within the material, that is, the phases of different impedance aids the internal multiple reflections of the EM radiation.…”
Section: Electromagnetic Interference Shielding Effectivenessmentioning
confidence: 99%
“…Kumar V et al [ 7 ] showed in research the electrical and mechanical properties of the composites improved significantly with the addition of the vapor grown carbon fiber (VGCF‐H) in Polyaniline‐Dodecylbenzenesulfonic acid/Divinylbenzene (PANI‐DBSA/DVB) composite. Electrical conductivity up to 300% improvement with the addition of 5 wt% VGCF‐H and the maximum flexural modulus is obtained at 3 wt% of VGCF‐H.…”
Section: Introductionmentioning
confidence: 99%